Penerapan Model Pembelajaran Tari Bambu dengan Media Kartu untuk Meningkatkan Prestasi Belajar Matematika - Mohamad Nur Fauzi (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
Bamboo dance learning model has advantages that can provide motivation to learn and exchange information during learning. But in the implementation of this learning model, the tendency of students to play is greater than learning. Therefore, it is necessary to modify the implementation of this learning model with the help of card media. This media contains questions and answers, so that each student will get one card in the form of questions or in the form of answers in turn. This type of research is classroom action research. Data feeder techniques used tests and observation sheets. From the results of this study it was concluded that student learning achievement increased from an average of 51 to 78.